Postintubation Sequels: Influence of Fluticasone and Technique of Intra-Operative Muscle Relaxation - Kayina, Choro Athiphro (Anesth Essays Res, 2018)
BACKGROUND: Postintubation sequels (PIS) are a cause of serious concern in the postoperative period. AIM: The aim of this study is to find the influence of preoperative inhaled steroid and technique of muscle relaxation on PIS. SETTINGS AND DESIGN: This prospective, exploratory pilot study was conducted on 120 adult American Society of Anesthesiologist physical status Class I and II patients undergoing general anesthesia (GA) with muscle relaxation and cuffed endotracheal tube (ETT) insertion. PATIENTS AND METHODS: Patients were randomized into four groups as follows: intermittent muscle relaxation with preanesthetic inhalation of either distilled water puffs (Group I(D)) or fluticasone puffs (Group I(F)); continuous infusion of muscle relaxant with preanesthetic inhalation of either distilled water puffs (Group C(D)) or fluticasone puffs (Group C(F)). After induction of GA, ETT was inserted. The intra-cuff pressure was maintained constant. The trachea was extubated in the light plane in intermittent groups and in the deep plane in continuous groups. STATISTICAL ANALYSIS: Qualitative parameters were compared using the Chi-square test and quantitative parameters using repeated measure ANOVA followed by Tukey's test. RESULTS: Group C(F) had significantly less incidence of sore throat and hoarseness compared to groups I(D) and I(F). The severity of sore throat was more in groups I(D) and I(F) than in groups C(F) and C(D) (P < 0.002). The severity of hoarseness was least in group C(F) (23.3%) and highest in group I(F) (90%). None of the patients had a cough in group C(F). The incidence and severity of dysphagia were significantly less in group C(F) as compared to other groups (P < 0.005 and P < 0.008, respectively). CONCLUSION: Continuous infusion of muscle relaxant with extubation in deep plane of anesthesia with preanesthetic inhalation of fluticasone puffs results in lesser incidence and severity of PIS.